Using Interleukin 6 and 8 in Blood and Bronchoalveolar Lavage Fluid to Predict Survival in Hematological Malignancy Patients With Suspected Pulmonary Mold Infection - Rawlings, Stephen A.; Heldt, Sven; Prattes, Juergen; Eigl, Susanne; Jenks, Jeffrey D.; Flick, Holger; Rabensteiner, Jasmin; Prüller, Florian; Wölfler, Albert; Neumeister, Peter; Strohmaier, Heimo; Krause, Robert; et al. (Frontiers in Immunology, 2019)
Background: Molds and other pathogens induce elevated levels of several cytokines, including interleukin (IL)-6 and IL-8. The objective of this study was to investigate the prognostic value of IL-6 and IL-8 as well as fungal biomarkers in blood and bronchoalveolar lavage fluid (BAL) for overall survival in patients with underlying hematological malignancies and suspected mold infection. Methods: This cohort study included 106 prospectively enrolled adult cases undergoing bronchoscopy. Blood samples were collected within 24 hours of BAL sampling and, in a subset of 62 patients, serial blood samples were collected up until 4 days after bronchoscopy. Biomarkers and cytokines were assayed in blood and BAL fluid and associations with overall mortality were assessed at the end of the study using receiver operating characteristic (ROC) curve analysis. Results: Both blood IL-8 and blood IL-6 as well as BAL IL-6 levels at the time of bronchoscopy were predictors of 30-day, 90-day and 180-day all-cause mortality. Increasing blood IL-6 levels between bronchoscopy and day four after bronchoscopy were significantly associated with higher 90-day mortality, with similar findings for increasing IL-8 levels. In ROC analysis the difference of blood IL-8 levels between four days after bronchoscopy and the day of bronchoscopy had an AUC of 0.829 (95%CI 0.71-0.95; p<0.001) for predicting 90-day mortality. Conclusions: Elevated levels of IL-6 and IL-8 in blood or BAL fluid at the time of bronchoscopy, and rising levels in blood four days following bronchoscopy were predictive of mortality in these patients with underlying hematological malignancy who underwent bronchoscopy for suspected mold infection.